Direct numerical simulation of nucleate boiling in micro-layer regime. (August 2018) - Urbano, A.; Tanguy, S.; Huber, G.; Colin, C.
Highlights: First DNS of nucleate pool boiling in micro-layer regime (fully resolved). Parametric study on the transition between micro-layer and contact line regimes. A micro-layer is formed if the growth of the bubble exceeds a limit velocity. The depletion is mainly induced by capillary actions. Correlation on the limit between micro-layer and contact line regimes. Abstract: The physical mechanisms associated with the evolution of a micro-layer beneath a bubble and the transition between contact line and micro-layer regimes are investigated with fully resolved numerical simulations, in the framework of nucleate pool boiling. Capturing the transition between these two regimes has been possible for the first time using very refined grids and parallel computations. Indeed, grids with a cell size under 1 μm must be used in order to capture thermal and dynamical effects in the micro-layer. Such multiscale computations require advanced code capabilities. The present simulations are used to analyse the physical processes involved in the formation and depletion of a micro-layer. A parametric study is carried out to investigate the impact of the main parameters affecting the presence of the micro-layer. From these results, the limit conditions between nucleate boiling in micro-layer and contact line regimes are deduced. Neglecting the micro-layer would lead to erroneous results because it has a strong influence on the overall bubble growth. Therefore the present results could be of major interest for designing models of nucleate pool boiling in larger scales computations, when the micro-layer cannot be resolved.